2020
DOI: 10.1007/s12274-020-3190-1
|View full text |Cite
|
Sign up to set email alerts
|

Porous rod-like Ni2P/Ni assemblies for enhanced urea electrooxidation

Abstract: The urea oxidation reaction has attracted increasing attention. Here, porous rod-like Ni 2 P/Ni assemblies, which consist of numerous nanoparticle subunits with matching interfaces at the nanoscale have been synthesized via a simple phosphating approach. Density functional theory calculations and density of states indicate that porous rod-like Ni 2 P/Ni assemblies can significantly enhance the activity of chemical bonds and the conductivity compared with NiO/Ni toward the urea oxidation reaction. The optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 63 publications
(69 reference statements)
0
26
0
Order By: Relevance
“…This result demonstrated that NC-FNCP has a faster charge transfer rate and favorable OER kinetics. TOF as a considerable kinetic parameter can be used to depict the intrinsic activities of electrocatalysts [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result demonstrated that NC-FNCP has a faster charge transfer rate and favorable OER kinetics. TOF as a considerable kinetic parameter can be used to depict the intrinsic activities of electrocatalysts [17].…”
Section: Resultsmentioning
confidence: 99%
“…To date, transition metal phosphides (TMPs), such as Ni 2 P [17,18], Fe 2 P [19], MoP [20] and CoP [21] have been attracted wide attention owing to their chemical stability, low-cost, and environmental friendliness [22]. Among them, nickel phosphide shows extraordinary electrocatalytic activity and stability for UOR [17,19,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to protect the environment, people are looking for the earth's resource rich and cost‐effective alternatives to meet the needs of electrochemical energy storage and conversion [40–43] . 2D MOF nanosheets were considered as model electrocatalysts in recent years.…”
Section: Catalysismentioning
confidence: 99%
“…MOFs have unique physicochemical properties owing to their specific morphologies and high specific surface areas [29][30][31][32][33][34][35]. They reveal many advantages in gas separation, fluorescence sensing, catalysis, electrochemistry, and other fields [36][37][38]. For example, Bai et al [36] reported Ni/Co bimetallic MOF nanoplates, which exhibited excellent oxygen evolution reaction electrocatalytic activity with a low overpotential of 256 mV at 10 mA cm −2 and a small Tafel slope of 81.8 mV dec −1 in KOH with long-term electrochemical stability for 3000 cyclic voltammetry (CV) cycles.…”
Section: Introductionmentioning
confidence: 99%